Analisis Yuridis Tindak Pidana Pencucian Uang (Studi Putusan No. 311/Pid.Sus/2018/Pn. Mdn) - Andika Pratama; Rizkan Zulyadi; Sri Pinem (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The panel of judges adjudicating the money laundering case found the defendant guilty of the crime of money laundering from the narcotics crime, and therefore sentenced the defendant to 7 (seven) years imprisonment. Based on this, the formulation of the problems in this study: 1) How are the legal rules regarding money laundering in Indonesia, 2) How is law enforcement against the crime of money laundering in the Medan District Court, 3) What is the basis for the judge's consideration in imposing crimes against money laundering offenders in the Decision Number 311 / Pid.sus / 2018 / PN. Mdn. The research method used is descriptive method, while the data analysis technique used is descriptive qualitative. The results showed that the crime of money laundering is regulated in Law no. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering (UU PP - TPPU). The threat of money laundering is regulated in Article 3, namely imprisonment for a maximum of 20 (twenty) years and a maximum fine of Rp. 10,000,000,000. The panel of judges at the District Court that adjudicates money laundering crimes acts decisively in imposing crimes, especially because the examination process usually receives public scrutiny, such as money laundering from narcotics and corruption crimes. The basis for the consideration that the panel of judges, the defendant has participated in the circulation of narcotics by receiving, transferring money as payment for narcotics, this is commonly done by the perpetrators of the Crime of Money Laundering to disguise or hide the origin of the proceeds of crime. However, the panel of judges had imposed a sentence that was too low on the defendant, namely 7 years in prison, far below the threat of money laundering in Article 3 of the TPPU Law where the defendant was found guilty, namely 20 years in prison.